Packaging structure of display screen, preparation process thereof, display screen and display device

CN123022077APending Publication Date: 2026-10-30HEFEI VISIONOX TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510559979.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本申请实施例的目的在于提供一种显示屏的封装结构及其制备工艺、显示屏及显示设备,以解决现有技术中静态封装结构在极端湿度或氨气浓度波动时阻隔效率大幅下降的缺陷

Benefits of technology

[0030]本申请提供的显示屏的封装结构及其制备工艺、显示屏及显示设备的有益效果在于:与现有技术相比,第二阻挡层中的吸附材料能够在环境中的有害物质浓度较高时,增大其吸附孔的孔径,以吸收和捕捉有害物质,同时弹性颗粒膨胀封堵吸附孔的孔口,将有害物质封堵在吸附材料内部;当环境中的有害物质浓度较低时,吸附孔的孔径恢复至较小的状态,以阻挡有害物质通过。通过动态响应环境中有害物质浓度的变化,有效提高了封装结构对有害物质的阻隔效果和可靠性,适用于极端湿度或氨气浓度波动的环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022077A_ABST
    Figure CN123022077A_ABST
Patent Text Reader

Abstract

The application provides a packaging structure of a display screen, a preparation process of the packaging structure, the display screen and a display device, and belongs to the technical field of display screens. The packaging structure comprises a packaging part and a blocking part covering the surface of the packaging part. The blocking part comprises a first blocking layer, a second blocking layer and a third blocking layer which are stacked. The first blocking layer is an inorganic layer. The third blocking layer is a conductive oxide layer. The second blocking layer comprises a polymer matrix, an adsorbing material and elastic particles. The adsorbing material has adsorbing holes for adsorbing harmful substances. When the concentration of the harmful substances is higher than a preset value, the pore size of the adsorbing holes increases to adsorb the harmful substances, and the elastic particles expand to block the adsorbing holes of the adsorbing material. When the concentration of the harmful substances is lower than the preset value, the pore size of the adsorbing holes of the adsorbing material restores to block the harmful substances. The packaging structure makes the display screen applicable to an environment with extreme humidity or ammonia concentration fluctuation, and improves the service life and reliability of the display screen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of display screens, and more specifically, relates to a display screen packaging structure and its manufacturing process, as well as a display screen and display device. Background Technology

[0002] Flexible organic light-emitting diodes (OLEDs) have significant application value in the field of flexible displays due to their bendability and thinness. However, flexible OLED devices are extremely sensitive to moisture and oxygen. Water and oxygen penetration from the external environment can lead to problems such as corrosion of internal electrodes and degradation of organic materials, severely reducing device lifespan. Therefore, thin-film encapsulation (TFE) technology has become a core component of flexible OLED manufacturing.

[0003] Current thin-film encapsulation technology employs an "inorganic-organic-inorganic" multilayer stacked structure. The lower inorganic layer is a dense silicon nitride / silicon oxide (SiNx / SiOx) layer formed by chemical vapor deposition (CVD) to serve as a basic water and oxygen barrier layer. The middle organic layer uses inkjet printing (IJP) to coat a polymer buffer layer, alleviating mechanical stress. The upper inorganic layer is then again deposited with silicon oxide / silicon nitride (SiOx / SiNx) to enhance the encapsulation effect. However, in this static encapsulation structure, the pore size of the inorganic layer is fixed, and the barrier efficiency drops significantly under extreme humidity or ammonia concentration fluctuations.

[0004] To address these issues, most current methods involve covering the barrier layer surface with a transparent polymer film to reduce permeation through physical barriers. However, this passive protection mechanism cannot respond to environmental changes and is prone to cracking and failure after bending. Another solution involves laser etching to create micropit structures on the barrier layer surface and filling them with adsorbent materials such as carbon nanotubes. These materials temporarily adsorb water and oxygen molecules due to their high specific surface area. However, this approach is complex, has high mass production costs, and the carbon nanotubes are prone to performance degradation due to adsorption saturation or oxidation, resulting in insufficient long-term reliability. Summary of the Invention

[0005] The purpose of this application is to provide a display screen packaging structure and its manufacturing process, as well as a display screen and display device, to solve the defect of the prior art where the barrier efficiency of static packaging structures drops significantly under extreme humidity or ammonia concentration fluctuations.

[0006] To achieve the above objectives, in a first aspect, this application provides a display screen encapsulation structure, including an encapsulation portion and a blocking portion covering the surface of the encapsulation portion, the blocking portion comprising:

[0007] The first barrier layer is an inorganic layer;

[0008] A second barrier layer, disposed on the side of the first barrier layer opposite to the encapsulation portion, includes a polymer matrix, an adsorbent material dispersed within the polymer matrix, and elastic particles dispersed within the polymer matrix. The adsorbent material has multiple adsorption pores for adsorbing harmful substances. When the concentration of the harmful substance is higher than a preset value, the pore size of the adsorption pores increases to adsorb the harmful substance, and the elastic particles expand to block the adsorption pores of the adsorbent material, thus trapping the harmful substance within the pores. When the concentration of the harmful substance is lower than the preset value, the pore size of the adsorption pores of the adsorbent material remains at its initial state, blocking the harmful substance. The harmful substances include water vapor and ammonia.

[0009] The third barrier layer is a conductive oxide layer and covers the side of the second barrier layer that is away from the first barrier layer.

[0010] In some embodiments of the first aspect, the adsorbent material is a zeolite molecular sieve.

[0011] In some embodiments of the first aspect, the second barrier layer further includes graphene quantum dots dispersed within the polymer matrix, the surface of which is modified with hydroxyl groups.

[0012] In some embodiments of the first aspect, the adsorbent material is mesoporous silica with an amino-modified surface.

[0013] In some embodiments of the first aspect, the elastic particle comprises alumina particles and a silica shell covering the outside of the alumina particles, and is located at the opening of the adsorption pore;

[0014] And / or, the preset values ​​include an ambient humidity of 30% to 50% RH and / or an ammonia concentration of 5 ppm to 10 ppm.

[0015] In some embodiments of the first aspect, the polymer matrix includes a cured matrix and a polyurethane-urea elastomer mixed in the cured matrix, the polyurethane-urea elastomer having dynamic disulfide bonds, and the concentration of the polyurethane-urea elastomer being 60% to 70%.

[0016] In some embodiments of the first aspect, the inorganic layer is a silicon nitride layer or a silicon oxide layer;

[0017] And / or, the thickness of the first barrier layer is 50nm to 100nm, the thickness of the second barrier layer is 2nm to 10nm, and the thickness of the third barrier layer is 5nm to 10nm;

[0018] And / or, the particle size of the adsorbent material is 50-200 nm, the pore size of the adsorption pores is 0.3 nm-0.5 nm, and the concentration of the adsorbent material in the polymer matrix is ​​20%-30%;

[0019] And / or, the elastic particles have a particle size of 10 nm to 20 nm, and the concentration of the elastic particles in the polymer matrix is ​​5% to 10%.

[0020] Secondly, this application provides a fabrication process for preparing the packaging structure as described in the first aspect and any embodiment thereof, comprising:

[0021] Prepare the first barrier layer;

[0022] A liquid polymer matrix is ​​prepared, and the adsorbent material and the elastic particles are mixed in the liquid polymer matrix to form a composite slurry;

[0023] The composite slurry is applied to the surface of the first barrier layer and then cured to form the second barrier layer.

[0024] The third barrier layer is prepared on the side of the second barrier layer that is opposite to the first barrier layer.

[0025] Secondly, this application provides a display screen, comprising:

[0026] substrate;

[0027] A display panel is disposed on one side surface of the substrate;

[0028] The encapsulation structure as described in the first aspect and any of its embodiments is disposed on the side surface of the display panel facing away from the substrate.

[0029] Thirdly, this application provides a display device, including the display screen provided in the second aspect embodiment.

[0030] The beneficial effects of the display screen packaging structure and its manufacturing process, as well as the display screen and display device provided in this application, are as follows: Compared with the prior art, the adsorbent material in the second barrier layer can increase the pore size of its adsorption pores when the concentration of harmful substances in the environment is high, so as to absorb and capture harmful substances. At the same time, the elastic particles expand and seal the pore openings of the adsorption pores, sealing the harmful substances inside the adsorbent material. When the concentration of harmful substances in the environment is low, the pore size of the adsorption pores returns to a smaller state to prevent harmful substances from passing through. By dynamically responding to changes in the concentration of harmful substances in the environment, the barrier effect and reliability of the packaging structure against harmful substances are effectively improved, making it suitable for environments with extreme humidity or fluctuating ammonia concentrations. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of the display device in the embodiments of this application;

[0033] Figure 2 This is a schematic diagram of the layer structure of the display screen in the left and right border directions in an embodiment of this application;

[0034] Figure 3 This is a schematic diagram of the layer structure of the display screen in the bottom direction in an embodiment of this application;

[0035] Figure 4 This is a schematic diagram of the display panel structure in an embodiment of this application;

[0036] Figure 5 This is a schematic diagram of the packaging structure in the embodiments of this application;

[0037] Figure 6 This is a schematic diagram of the structure of the blocking part in an embodiment of this application;

[0038] Figure 7 This is a schematic diagram of the structure of the blocking part in another embodiment of this application.

[0039] The following are the labeling elements in the figure:

[0040] 10 - Display device; 100 - Display screen; 200 - Mid-frame; 300 - Back cover;

[0041] 110-Substrate; 120-Display panel; 121-Display area; 122-Vertical scanning area; 123-Interval area; 124-PVEE wiring area; 125-Demultiplexing area; 126-Fan-out area; 127-Chip-on-chip thin film area; 128-Bending area; 130-Planing layer; 140-Pixel definition layer; 150-Reference electrode; 160-Cathode; 170-Common electrode; 180-Packaging structure; 190-Polarizer; 181-Packaging section; 1811-Silicon nitride layer; 1812-Inkjet printing layer; 1813-Silicon oxide layer; 182-Blocking section; 1821-First blocking layer; 1822-Second blocking layer; 1822a-Polymer matrix; 1822b-Adsorbent material; 1822c-Elastic particles; 1822d-Graphene quantum dots; 1823-Third blocking layer. Detailed Implementation

[0042] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of this application.

[0043] It should be noted that when a component is referred to as being "fixed to" or "set on" another component, it can be directly on or indirectly on that other component. When a component is referred to as being "connected to" another component, it can be directly connected to or indirectly connected to that other component.

[0044] It should be understood that the terms "length", "width", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0045] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0046] This application provides a display device, which can be any product or component with display function, such as a mobile phone, tablet computer, television, monitor, laptop computer, digital photo frame, or navigator.

[0047] Reference Figure 1The display device 10 includes a display screen 100, a middle frame 200, and a rear shell 300. The display screen 100 is disposed inside the middle frame 200, which supports the display screen 100. The rear shell 300 is connected to one side of the middle frame 200 and protects the display screen 100 and the middle frame 200, as well as other internal structures. The display screen 100 can be a flexible display screen 100 or a rigid display screen 100. The flexible display screen 100 can be an OLED flexible display screen 100, a quantum dot light emitting diode (QLED) flexible display screen 100, or an active-matrix organic light-emitting diode (AMOLED) flexible display screen 100. When a flexible display screen 100 is used, the middle frame 200 and the rear shell 300 in the display device 10 can be bendable or foldable structures.

[0048] Reference Figure 2 and Figure 3 The display screen 100 includes a substrate 110, a display panel 120, a planarization layer 130, a pixel definition layer 140, a reference electrode 150, a cathode 160, a common electrode 170, a packaging structure 180, and a polarizer 190, which are stacked from bottom to top.

[0049] The substrate 110 serves as the basic support for the encapsulation structure 180. When the display screen 100 is a rigid display screen 100, the substrate 110 can be a rigid substrate 110, such as a glass substrate 110; when the display screen 100 is a flexible display screen 100, the substrate 110 can be a flexible substrate 110, such as a polyimide (PI) substrate 110. The display panel 120 is used to display images. The planarization layer 130 is used to fill the unevenness on the surface of the substrate 110, ensuring the planarity of subsequent layer structures; the pixel definition layer 140 is used to define pixel areas. The reference electrode 150, cathode 160, and common electrode 170 work together to control the pixels of the display panel 120. The encapsulation structure 180 is used to protect the display panel 120 from damage caused by external environmental factors such as moisture and oxygen. The polarizer 190 can be bonded to the encapsulation structure 180 through an OCA adhesive layer to improve the display effect of the display panel 120.

[0050] Reference Figure 4The display panel 120 has a display area 121 and a non-display area 121. The display area 121 is used to display images, and the non-display area 121 is used for internal wiring and other device settings within the display panel 100. The display area 121 can be located in the center of the display panel 100, and the non-display area 121 surrounds the display area 121. The non-display area 121 may include a vertical scanning region 122, a spacing region 123, a PVEE wiring region 124, a demultiplexing region 125, a fan-out region 126, and a flip-chip thin film region 127. The vertical scanning region 122 is used to set up the vertical scanning region (VSR) circuit, which controls the row scanning of pixels in the display panel 120. The spacing region 123 is located between the vertical scanning region 122 and the display area 121, and is used to isolate the vertical scanning circuit from the display area 121 to prevent interference from the circuit to the displayed image. The PVEE wiring region 124 is used to set up the wiring of the pixel voltage electrodes to ensure that each pixel can receive the correct voltage signal. The demultiplexing area 125 is used to demultiplex signals from the driving circuit to control each pixel separately. The fan-out area 126 is located at the edge of the display area 121 and is used to lead signals from the display driver to the non-display area 121 for connection with the pixel electrodes in the display panel 120. The flip-chip area 127 is used to mount integrated circuit chips, which are connected to electrodes on the display panel 120 through anisotropic conductive films to realize signal transmission and control.

[0051] When the display screen 100 is a flexible display screen 100, it may also have a bending region 128 to enable bending or folding within the entire area. The bending region 128 may be located on one or both edges of the display screen 100, and may be positioned between the display area 121 and the non-display area 121, or entirely within the non-display area 121. The design of the bending region 128 allows the display screen 100 to bend or fold while maintaining its display function, thus making it suitable for more diverse electronic device forms, such as foldable screen phones and wearable devices.

[0052] The encapsulation structure 180 of the display screen 100 provided in this embodiment includes an encapsulation portion 181 and a blocking portion 182 covering the surface of the encapsulation portion 181.

[0053] The encapsulation section 181 is used to encapsulate and fix the display panel 120. The encapsulation section 181 can employ a conventional thin-film encapsulation (TFE) structure, which uses alternating stacks of inorganic and organic layers to form an effective barrier against moisture and oxygen. The inorganic layers can be made of silicon nitride (SiN). xThe encapsulation layer consists of silicon dioxide (SiOx) or a combination thereof, forming a dense thin film using chemical vapor deposition to provide basic water and oxygen barrier properties. The organic layer, which can be made of polymer materials, is formed through coating or printing processes to alleviate mechanical stress generated during encapsulation, while also increasing the flexibility and adaptability of the encapsulation structure. (See reference...) Figure 5 In this embodiment, the packaging portion 181 includes silicon nitride (SiN) layers stacked sequentially from bottom to top. x 1811, Inkjet Printing (IJP) layer 1812 and silicon oxide layer (SiOx) 1813.

[0054] Reference Figure 6 The blocking part 182 includes a first blocking layer 1821, a second blocking layer 1822 and a third blocking layer 1823 stacked from bottom to top.

[0055] The first barrier layer 1821 is an inorganic layer used to inhibit the permeation of water and oxygen molecules. In this embodiment, the inorganic layer can be a silicon nitride layer or a silicon oxide layer. The first barrier layer 1821 can be implemented using a chemical vapor deposition (CVD) or physical vapor deposition (PVD) process, forming a dense basic barrier layer by depositing silicon nitride or silicon oxide material. Optionally, the thickness of the first barrier layer 1821 can be 50 nm to 100 nm.

[0056] The second barrier layer 1822 is disposed between the first barrier layer 1821 and the third barrier layer 1823, and is used to adsorb harmful substances in the environment, including water vapor and ammonia. The second barrier layer 1822 can dynamically respond to environmental changes and adapt its blocking effect according to fluctuations in humidity, ammonia concentration, or other parameters in the environment, so as to better block and capture harmful substances. Optionally, the thickness of the second barrier layer 1822 can be 2 nm to 10 nm.

[0057] The third barrier layer 1823 is used to further enhance the barrier capability of the encapsulation structure 180 of the display screen 100. In this embodiment, the third barrier layer 1823 is a conductive oxide layer, which is an oxide film with both conductivity and barrier properties, such as an ultra-thin ITO conductive layer, formed by sputtering or vapor deposition processes, to improve the conductivity and barrier properties of the encapsulation structure 180, while preventing static electricity accumulation from damaging the display panel 120. Optionally, the thickness of the third barrier layer 1823 can be 5nm to 10nm.

[0058] The second barrier layer 1822 includes a polymer matrix 1822a, an adsorbent material 1822b dispersed within the matrix, and elastic particles 1822c dispersed within the polymer matrix 1822a. The adsorbent material 1822b has multiple adsorption pores for adsorbing harmful substances. When the concentration of harmful substances is higher than a preset value, the pore size increases to adsorb the harmful substances, and the elastic particles 1822c expand, blocking the adsorption pores and trapping the harmful substances within them. When the concentration of harmful substances is lower than the preset value, the pore size of the adsorbent material 1822b returns to its initial state, blocking the harmful substances. The harmful substances are water vapor and ammonia, and the preset values ​​may include an ambient humidity of 30%–50% RH and an ammonia concentration of 5 ppm–10 ppm.

[0059] The polymer matrix 1822a can be an organic polymer material used to contain the adsorbent material 1822b and the elastic particles 1822c, which are uniformly dispersed within the polymer matrix 1822a. The adsorbent material 1822b has a porous structure, with each adsorbent material 1822b possessing numerous adsorption pores for capturing and adsorbing harmful substances such as water vapor and ammonia. The elastic particles 1822c are nanoparticles with a certain degree of elasticity, capable of expanding when the ambient humidity and ammonia concentration are higher than preset values, and contracting when the ambient humidity and ammonia concentration are lower than preset values.

[0060] Specifically, when the concentration of harmful substances in the environment is low, the pore size of the adsorption pores on the adsorption material 1822b is small, which can block water vapor and ammonia from passing through. When the concentration of harmful substances in the environment is high, the pore size of the adsorption pores on the adsorption material 1822b increases, absorbing ammonia into the inside of the adsorption pores. At the same time, the elastic particles 1822c can absorb water vapor and expand. The elastic particles 1822c are located at the opening of the adsorption pores. After the elastic particles 1822c expand, they can block the adsorption pores, thus locking the ammonia inside the adsorption pores. When the concentration of harmful substances in the environment decreases again, the elastic particles 1822c shrink back to their initial state, and the ammonia in the adsorption pores will be released back to the outside due to the low external concentration. At this time, the pore size of the adsorption pores of the adsorption material 1822b returns to its initial small state, once again blocking water vapor and ammonia. Through this design, the second barrier layer 1822 can dynamically adjust its barrier performance according to the concentration of harmful substances in the environment, thereby more effectively protecting the display panel 120 from harmful substances such as water vapor and ammonia.

[0061] Through the synergistic effect of the elastic particles 1822c and the adsorption pores in the adsorption material 1822b, the encapsulation structure 180 can adaptively adjust its adsorption capacity according to environmental changes, effectively coping with extreme humidity or ammonia concentration fluctuations. Simultaneously, the flexibility of the polymer matrix 1822a and the stress-buffering effect of the elastic particles 1822c can reduce the impact of mechanical stress on the inorganic layer, inhibiting microcrack formation and interface delamination. Furthermore, when the display device is bent, the flexibility of the polymer matrix 1822a can alleviate stress concentration, while the deformation of the elastic particles 1822c can absorb some mechanical stress, reducing the impact on the inorganic layer. The conductive oxide material of the third barrier layer 1823 provides additional physical barrier while maintaining necessary conductivity, meeting the functional requirements of flexible displays. It maintains excellent water and oxygen barrier performance under dynamic environments while possessing good mechanical durability, significantly improving the reliability and lifespan of flexible display devices.

[0062] In some embodiments, the adsorbent 1822b is a zeolite molecular sieve.

[0063] Zeolite molecular sieves are aluminosilicate crystalline materials with adsorption properties. They possess a large number of uniform and minute pores, forming multiple adsorption pores. The size and shape of these pores allow for selective adsorption and separation of specific molecules or ions. The pore size of the zeolite molecular sieve matches that of the adsorbent material 1822b, enabling efficient capture and adsorption of water vapor and ammonia molecules in the environment, further enhancing the barrier properties of the display screen 100's encapsulation structure 180. For example, the pore size range of type 3A molecular sieves can be controlled within 0.3-0.4 nm, and that of type 5A molecular sieves within 0.5-0.55 nm. Simultaneously, zeolite molecular sieves exhibit excellent thermal and chemical stability, maintaining stable adsorption performance under various extreme environments, thus ensuring the long-term reliability and service life of the display screen 100.

[0064] When the environmental concentration is higher than the preset value, the pore size of the microporous structure of the zeolite molecular sieve will expand appropriately, thereby capturing harmful substances more effectively. When the concentration of harmful substances in the environment decreases, the rigid framework structure of the zeolite molecular sieve enables the adsorption pores to quickly return to the initial pore size to block harmful substances.

[0065] The microporous structure of zeolite molecular sieves remains stable during dynamic adjustment, and its rigid framework can withstand repeated extrusion deformation. For example, during the bending process of the flexible substrate 110, the chemical stability of the zeolite molecular sieve can prevent pore collapse caused by bending stress or high-temperature processes. Optionally, the adsorbent 1822b is selected from ZSM-5 type zeolite molecular sieves. In the preparation process, ZSM-5 molecular sieve powder is first mixed with polymer matrix 1822a, and the molecular sieve is uniformly distributed in the polymer matrix 1822a by ultrasonic dispersion technology. Then, the mixture is coated on the surface of the first barrier layer 1821 by spin coating or inkjet printing to form the second barrier layer 1822.

[0066] Reference Figure 7 Furthermore, the second barrier layer 1822 also includes graphene quantum dots (GQDs) 1822d dispersed within the polymer matrix 1822a, the surface of which is modified with hydroxyl groups (-OH).

[0067] Graphene quantum dots 1822d can be prepared by chemical vapor deposition followed by surface hydroxylation treatment. The graphene quantum dots 1822d are mixed with a polymer matrix 1822a, an adsorbent material 1822b, and elastic particles 1822c, and after being uniformly dispersed by stirring, they are coated into a film to form a second barrier layer 1822. The particle size of the graphene quantum dots 1822d can be selected in the range of 5-10 nm, and the density of surface hydroxyl groups can be controlled at 1.5-2.5 per square nanometer.

[0068] Hydroxyl groups can interact with hydrogen bonds in ammonia gas, thereby improving the adsorption efficiency and selectivity of ammonia molecules. When the concentration of harmful substances in the environment increases, the hydroxyl groups on the surface of graphene quantum dots 1822d combine with hydrogen bonds in ammonia molecules, further promoting the expansion of the pores of the zeolite molecular sieve, increasing the effective pore size of the adsorption pores, and improving the capture and adsorption capacity of the adsorbent material 1822b for harmful substances. Specifically, when the ambient humidity or ammonia concentration exceeds a preset value, the pore size of the adsorption pores expands to absorb ammonia gas. The hydrogen bond interaction between the hydroxyl groups on the surface of graphene quantum dots 1822d and the ammonia gas entering the adsorption pores enhances the capture efficiency of ammonia molecules, further improving the response capability of the barrier part 182 to extreme environmental fluctuations.

[0069] In some embodiments, the adsorbent 1822b is mesoporous silica with an amino-modified surface.

[0070] Mesoporous silica is a silicon-based material with a high specific surface area and uniform pores. By modifying its surface with amino groups (-NH2), these groups can reverse bind with ammonia molecules, achieving adsorption of ammonia. Simultaneously, the amino groups also enhance the material's affinity for water molecules, thereby improving its water vapor adsorption capacity. Compared to the combination of zeolite molecular sieves and graphene quantum dots 1822d, using surface-modified amino-based mesoporous silica offers the advantage of lower cost while maintaining adsorption capacity.

[0071] Mesoporous silica, possessing a regular hexagonal pore structure, can be synthesized via a hydrothermal method. After synthesis, the mesoporous silica is immersed in an ethanol solution of 3-aminopropyltriethoxysilane for surface amination modification. In preparing the second barrier layer 1822, the amino-modified mesoporous silica powder is mixed with the polymer matrix 1822a and elastic particles 1822c, and ultrasonic dispersion and stirring are performed to ensure uniform dispersion of all components. Subsequently, the mixture is coated onto the surface of the first barrier layer 1821 using methods such as spin coating, doctor blade coating, or inkjet printing to form the second barrier layer 1822 with dynamic adjustment capabilities.

[0072] In addition, the adsorbent 1822b can also be a metal-organic framework (MOF), a covalent organic framework (COF), a porous organic polymer (POP), a carbon-based porous material (activated carbon, carbon nanotube sponge or graphene aerogel, etc.) or a bio-based porous material (porous cellulose, chitosan aerogel or porous starch, etc.).

[0073] In some embodiments, the elastic particle 1822c includes alumina particles and a silica shell covering the outside of the alumina particles.

[0074] Alumina particles, being an inorganic material with high hardness and good elasticity, provide stable mechanical support and responsiveness to environmental changes. The silica shell, possessing excellent chemical stability and flexibility, protects the internal alumina particles from external environmental corrosion while enhancing the compatibility and bonding between the elastic particles 1822c and the polymer matrix 1822a. The alumina particles, acting as the core, maintain structural integrity during expansion and contraction due to their high hardness, preventing particle breakage caused by repeated deformation. The silica shell forms chemical bonds with the polymer matrix 1822a through surface hydroxyl groups, enhancing interfacial bonding strength. The core-shell structure of alumina and silica is connected through chemical bonds or van der Waals forces, ensuring the stability of the shell and core during dynamic deformation.

[0075] Specifically, the alumina core provides rigid support under bending stress, inhibiting the propagation of internal cracks in the particles, while the silica shell forms covalent bonds with the carboxyl or epoxy groups of the polymer matrix 1822a through hydroxyl groups, increasing the displacement resistance of the particles in the matrix. When changes in environmental concentration trigger volume changes in the elastic particles 1822c, the core-shell interface buffers the stress through pre-established chemical bonds, preventing the shell from peeling off from the core.

[0076] Alumina particles can be prepared via a sol-gel method, where an alumina precursor solution is hydrolyzed and condensed under controlled temperature conditions to form nanoscale alumina particles. Subsequently, a silica shell is grown on the surface of the alumina particles using a surface modification method. Specifically, the prepared alumina particles are dispersed in an ethanol solution, and tetraethyl orthosilicate (TEOS) is added as a silica precursor. A hydrolysis reaction is then carried out under alkaline conditions to form a uniform silica shell layer on the surface of the alumina particles. The thickness of the silica shell can be controlled by adjusting the reaction time and the amount of TEOS used. Finally, the core-shell structured composite elastic particles 1822c are mixed with a polymer matrix 1822a and dispersed uniformly by stirring to prepare a second barrier layer 1822.

[0077] Through the above technical solution, the core-shell structure of the composite elastic particles 1822c maintains the dynamic response capability to environmental humidity and ammonia concentration, and improves the structural stability under repeated bending conditions, thereby effectively avoiding the structural damage of the second barrier layer 1822 and the formation of permeation channels, and extending the service life of the flexible display screen 100.

[0078] Furthermore, the elastic particles 1822c can also be polymer hydrogel nanoparticles, hydrophilic MOF particles, or silane coupling agent-modified zirconia nanoparticles. Among these, polymer hydrogel nanoparticles exhibit excellent water absorption and retention properties, enabling rapid response to humidity changes and adjustment of the pore size of the adsorbent material 1822b. Hydrophilic MOF particles, due to their ordered pore structure and adjustable pore size, demonstrate excellent adsorption and separation performance for specific water vapor or ammonia molecules. Silane coupling agent-modified zirconia nanoparticles combine the hardness of inorganic materials with the flexibility of organic modifications, improving the compatibility and bonding force between the particles and the polymer matrix 1822a.

[0079] Optionally, the particle size of the adsorbent 1822b is 50-200 nm, the pore size of the adsorption pores is 0.3 nm-0.5 nm, and the concentration of the adsorbent 1822b in the polymer matrix 1822a is 20%-30%.

[0080] Optionally, the particle size of the elastic particles 1822c is 10 nm to 20 nm, and the concentration of the elastic particles 1822c in the polymer matrix 1822a is 5% to 10%.

[0081] By limiting the pore size and concentration of the adsorbent material 1822b, and the particle size and concentration of the elastic particles 1822c, a matching relationship is established between the pore size of the adsorbent material 1822b and the expansion and contraction amplitude of the elastic particles 1822c. A pore size range of 0.3 nm to 0.5 nm effectively traps these harmful substances. Furthermore, as the concentration of harmful substances in the environment increases, the elastic particles 1822c are allowed to expand at the pore openings, effectively sealing them and achieving a good effect in capturing and blocking harmful substances. A 20% to 30% adsorbent material concentration ensures sufficient adsorption sites, while a 5% to 10% elastic particle concentration balances response speed and mechanical stability, avoiding material breakage or performance degradation due to excessive expansion.

[0082] In some embodiments, the polymer matrix 1822a is a self-healing polymer, which can repair itself under preset conditions through dynamic covalent bonds or non-covalent interactions.

[0083] The self-healing polymer can include at least one of dynamic covalent bonds or non-covalent interactions. Dynamic covalent bonds include Diels-Alder reaction bonds or disulfide bonds, while non-covalent interactions include hydrogen bonds, ionic interactions, or π-π stacking interactions. Dynamic covalent bonds undergo reversible breakage and recombination under a preset temperature or specific wavelength of light. For example, Diels-Alder reaction bonds break in reverse reaction at 60-80℃ and re-crosslink at 20-40℃. Non-covalent interactions spontaneously recombine after mechanical stress is released through inter-chain physical forces. The repair capability of the self-healing polymer is related to the distribution of the adsorbent material 1822b and the elastic particles 1822c. When the polymer matrix 1822a cracks due to bending, the local stress concentration of the elastic particles 1822c in the crack area accelerates the breakage and recombination process of dynamic bonds. Simultaneously, the adsorbent material 1822b reduces impurity interference at the crack interface by adsorbing water molecules or ammonia molecules from the environment, promoting the rearrangement of molecular chains.

[0084] During the bending process of the display screen 100, microcracks in the polymer matrix 1822a cause interfacial separation between the adsorbent material 1822b and the elastic particles 1822c. At this point, a reversible reaction of dynamic bonds is activated by applying preset conditions, such as local heating of the crack area to 60°C or irradiation with 365nm ultraviolet light. The dynamic covalent bonds break, the molecular chains gain mobility and refill the crack gaps, and subsequently, under cooling or after the light irradiation stops, the dynamic bonds re-crosslink, restoring the integrity of the matrix. During this process, the expansion and contraction function of the elastic particles 1822c is maintained due to matrix repair, and the dynamic adjustment capability of the adsorbent pores prevents pore size loss due to cracks. Non-covalent interactions automatically repair microcracks through intermolecular forces in the absence of external stimuli; for example, after hydrogen bonds are broken by external forces, the molecular chains reform a hydrogen bond network through thermal motion. This allows the second barrier layer 1822 to effectively block water and oxygen permeation even after multiple bends, without the need for external repair agents or complex processes, thus improving the long-term reliability of the encapsulation structure 180.

[0085] Optionally, the polymer matrix 1822a includes a cured matrix and a polyurethane-urea elastomer mixed in the cured matrix, the polyurethane-urea elastomer having dynamic disulfide bonds, and the concentration of the polyurethane-urea elastomer being 60% to 70%.

[0086] The curing matrix is ​​a thermosetting or thermoplastic polymer such as polyurethane, epoxy resin or polyimide. For example, the curing matrix is ​​UV-curable polyurethane, which achieves rapid cross-linking and curing under ultraviolet light irradiation through a UV photoinitiator.

[0087] Polyurethane-urea elastomers are self-healing materials capable of self-repair under predetermined conditions. Specifically, the disulfide bonds in polyurethane-urea elastomers can undergo reversible breakage when heated to a certain temperature (e.g., 80-100℃) or under specific wavelength light irradiation, forming sulfur free radicals. Subsequently, upon cooling or cessation of light irradiation, the sulfur free radicals recombine to form disulfide bonds, achieving self-repair of the matrix. This process not only repairs microcracks caused by bending but also maintains the flexibility and elasticity of the polymer matrix 1822a, ensuring the integrity of the encapsulation structure 180 remains undamaged.

[0088] Furthermore, polyurethane-urea elastomers possess excellent chemical stability and mechanical strength, enabling them to meet the demands of flexible display devices in complex environments. During the dynamic use of the display screen 100, the introduction of the self-healing polymer significantly enhances the barrier capability of the second barrier layer 1822 against water and oxygen permeation, extending the lifespan of the flexible display device while reducing repair costs due to damage to the encapsulation structure 180.

[0089] During the curing process, the cured matrix and polyurethane-urea elastomer can form a cross-linked network structure, which improves the mechanical properties and chemical corrosion resistance of the polymer matrix (1822a). During the use of the display screen 100, even if it is subjected to impact from the external environment or corrosion by chemicals, the second barrier layer 1822 can still maintain its structural integrity and functional stability, effectively extending the service life of the display screen 100.

[0090] In preparing the second barrier layer, a liquid mixture of a curable matrix and a polyurethane-urea elastomer is first uniformly mixed with adsorbent material 1822b and elastic particles 1822c. This mixture is then applied to the surface of the first barrier layer 1821 using methods such as coating or spin coating. Subsequently, the coating is rapidly cured using ultraviolet (UV) irradiation, forming a self-healing second barrier layer 1822. The UV curing process not only improves production efficiency but also ensures the uniformity and density of the coating structure, further enhancing the barrier ability of the second barrier layer 1822 against water and oxygen permeation.

[0091] This application embodiment also provides a fabrication process for preparing the packaging structure 180 in the above embodiments, including the following steps:

[0092] Step S101: Prepare the encapsulation part 181.

[0093] Specifically, the packaging section 181 is a thin film encapsulation (TFE) structure, including silicon nitride (SiN) layers stacked sequentially from bottom to top. × The package 181 consists of an inkjet printing layer (IJP) 1811, an inkjet printing layer (IJP) 1812, and a silicon oxide layer (SiOx) 1813. In fabricating the package 181, a silicon nitride layer 1811 is first formed on a substrate material using chemical vapor deposition (CVD). The silicon nitride layer 1811 serves as the bottom layer and provides excellent moisture barrier properties. Subsequently, an inkjet printing layer 1812 is formed on the silicon nitride layer 1811 using inkjet printing technology. The inkjet printing layer 1812 is composed of organic materials, and uniformity and patterning of the layer thickness can be achieved by precisely controlling the deposition position and number of ink droplets. Finally, a silicon oxide layer 1813 is formed on the inkjet printing layer 1812 using physical vapor deposition (PVD) or chemical vapor deposition (CVD). The silicon oxide layer 1813 serves as the top layer, further enhancing the moisture barrier capability of the package 181. The stacked structure of silicon nitride layer 1811, inkjet printing layer 1812 and silicon oxide layer 1813 forms a dense thin film encapsulation structure, which effectively blocks the penetration of water vapor and oxygen.

[0094] In step S102, a first barrier layer 1821 is prepared on one side surface of the encapsulation portion 181.

[0095] Specifically, the first barrier layer 1821 is a silicon nitride layer or a silicon oxide layer. The first barrier layer 1821 is formed on the side surface of the package portion 181 opposite to the display panel 120 using physical vapor deposition (PVD) or chemical vapor deposition (CVD) processes.

[0096] Step S103: Prepare a liquid polymer matrix 1822a, and mix the adsorbent material 1822b and elastic particles 1822c into the liquid polymer matrix 1822b to form a composite slurry.

[0097] Specifically, the polymer matrix 1822a includes a cured matrix and a polyurethane-urea elastomer mixed within the cured matrix. In preparing the liquid polymer matrix 1822a, the cured matrix and the polyurethane-urea elastomer are first mixed in a certain proportion and stirred to form a homogeneous liquid mixture. Subsequently, the adsorbent material 1822b and elastic particles 1822c are added to the liquid mixture according to a set concentration range. High-speed dispersion and ultrasonic treatment are then used to ensure that the adsorbent material 1822b and elastic particles 1822c are uniformly dispersed in the polymer matrix 1822a, avoiding agglomeration.

[0098] Step S104: Apply the composite paste to the surface of the first barrier layer 1821 facing away from the encapsulation part 181, and allow the composite paste to cure to form the second barrier layer 1822.

[0099] Specifically, after the liquid polymer matrix 1822a, adsorbent material 1822b, and elastic particles 1822c are uniformly mixed to form a composite slurry, the composite slurry is uniformly coated onto the surface of the first barrier layer 1821 by methods such as coating, spin coating, or spraying. During the coating process, the uniformity and density of the second barrier layer 1822 can be ensured by controlling the coating speed and thickness. In this embodiment, the curing substrate is UV-curable polyurethane. After coating, the liquid polymer matrix 1822a can be rapidly cured by ultraviolet irradiation to form the second barrier layer 1822 with dynamic response and self-healing capabilities.

[0100] In step S105, a third barrier layer 1823 is prepared on the side of the second barrier layer 1822 opposite to the first barrier layer 1821. In this embodiment, the third barrier layer 1823 is a conductive oxide layer, such as an ultrathin ITO conductive layer, and can be prepared by magnetron sputtering or vapor deposition.

[0101] In summary, the encapsulation structure 180 of the display screen 100 provided in this application embodiment achieves comprehensive optimization by combining dynamically responsive elastic particles 1822c, highly efficient adsorbent material 1822b, and a self-healing polymer matrix 1822a. Under various dynamic conditions such as changes in environmental humidity, ammonia concentration, and bending of the display screen 100, this encapsulation structure 180 can maintain excellent barrier performance, effectively preventing water and oxygen penetration and ensuring the long-term stability and reliability of the flexible display device.

[0102] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A display screen packaging structure, characterized in that, The package includes a packaging portion (181) and a blocking portion (182) covering the surface of the packaging portion (181), the blocking portion (182) including: The first barrier layer (1821) is an inorganic layer; A second barrier layer (1822) is disposed on the side of the first barrier layer (1821) away from the encapsulation part (181), comprising a polymer matrix (1822a), an adsorbent material (1822b) dispersed inside the polymer matrix (1822a), and elastic particles (1822c) dispersed inside the polymer matrix (1822a); the adsorbent material (1822b) has a plurality of adsorption pores for adsorbing harmful substances; when the concentration of the harmful substance is higher than a preset value, the pore size of the adsorption pores increases to adsorb the harmful substance, and the elastic particles (1822c) expand to block the adsorption pores of the adsorbent material (1822b), thus locking the harmful substance inside the adsorption pores; when the concentration of the harmful substance is lower than the preset value, the pore size of the adsorption pores of the adsorbent material (1822b) is in its initial state, blocking the harmful substance; wherein, the harmful substance includes water vapor and ammonia. The third barrier layer (1823) is a conductive oxide layer and covers the side of the second barrier layer (1822) opposite to the first barrier layer (1821).

2. The display screen packaging structure according to claim 1, characterized in that, The adsorbent material (1822b) is a zeolite molecular sieve.

3. The display screen packaging structure according to claim 2, characterized in that, The second barrier layer (1822) further includes graphene quantum dots (1822d) dispersed within the polymer matrix (1822a), the surface of which is modified with hydroxyl groups.

4. The display screen packaging structure according to claim 1, characterized in that, The adsorbent material (1822b) is mesoporous silica with amino groups modified on its surface.

5. The display screen packaging structure according to claim 1, characterized in that, The elastic particle (1822c) includes alumina particles and a silica shell covering the outside of the alumina particles, and is located at the opening of the adsorption pore; And / or, the preset values ​​include an ambient humidity of 30% to 50% RH and / or an ammonia concentration of 5 ppm to 10 ppm.

6. The display screen packaging structure according to claim 1, characterized in that, The polymer matrix (1822a) includes a cured matrix and a polyurethane-urea elastomer mixed in the cured matrix, the polyurethane-urea elastomer having dynamic disulfide bonds, and the concentration of the polyurethane-urea elastomer being 60% to 70%.

7. The packaging structure of the display screen according to any one of claims 1-6, characterized in that, The inorganic layer is a silicon nitride layer or a silicon oxide layer; And / or, the thickness of the first barrier layer is 50nm to 100nm, the thickness of the second barrier layer is 2nm to 10nm, and the thickness of the third barrier layer is 5nm to 10nm; And / or, the particle size of the adsorbent material (1822b) is 50-200 nm, the pore size of the adsorption pores is 0.3 nm-0.5 nm, and the concentration of the adsorbent material (1822b) in the polymer matrix (1822a) is 20%-30%; And / or, the elastic particles (1822c) have a particle size of 10 nm to 20 nm, and the concentration of the elastic particles (1822c) in the polymer matrix (1822a) is 5% to 10%.

8. A fabrication process for a packaging structure for a display screen as described in any one of claims 1-7, characterized in that, include: Prepare the encapsulation part (181); The first barrier layer (1821) is prepared on one side surface of the encapsulation portion (181); A liquid polymer matrix (1822a) is prepared, and the adsorbent material (1822b) and the elastic particles (1822c) are mixed in the liquid polymer matrix (1822b) to form a composite slurry; The composite slurry is applied to the surface of the first barrier layer (1821) away from the encapsulation part (181), and the composite slurry is cured to form the second barrier layer (1822); The third barrier layer (1823) is prepared on the side of the second barrier layer (1822) opposite to the first barrier layer (1821).

9. A display screen (100), characterized in that, include: substrate(110); A display panel (120) is disposed on one side surface of the substrate (110); The encapsulation structure (180) as described in any one of claims 1-7 is disposed on the side surface of the display panel (120) facing away from the substrate (110).

10. A display device (10), characterized in that, Includes the display screen (100) as described in claim 9.